2013
DOI: 10.1016/j.drugalcdep.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

National trends in pharmaceutical opioid related overdose deaths compared to other substance related overdose deaths: 1999–2009

Abstract: Background: Pharmaceutical opioid related deaths have increased. This study aimed to place pharmaceutical opioid overdose deaths within the context of heroin, cocaine, psychostimulants, and pharmaceutical sedative hypnotics, examine demographic trends, and describe common combinations of substances involved in opioid related deaths. Methods: We reviewed deaths among 15-64 year olds in the US from 1999-2009 using death certificate data available through the CDC Wide-Ranging Online Data for Epidemiologic Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
239
3
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(252 citation statements)
references
References 41 publications
8
239
3
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Greater opioid prescribing contributed to increased opioid availability for abuse and overdose. [12][13][14] Primary care physicians (PCPs) and internists prescribe the majority of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Greater opioid prescribing contributed to increased opioid availability for abuse and overdose. [12][13][14] Primary care physicians (PCPs) and internists prescribe the majority of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Between the years 1999-2010, rates of opioid sales, deaths, and treatment admission have each more than tripled. 1 In the same period of time, overdose deaths from pharmaceutical opioids represented the highest relative increase of overdose death rates among all drug types in the United States, with a nearly 4-fold increase.…”
Section: Introductionmentioning
confidence: 99%
“…19 Calcaterra and colleagues reported that opioids plus benzodiazepines were the most common cause of polysubstance overdose deaths in a national study from 1999 to 2009, and increased the risk of drug overdose associated with opioids. 1 In our cohort, benzodiazepines significantly increased the risk of overdose but did not disproportionately affect persons with mental health disorders. However, we did find that the odds of overdose progressively rose with longer duration of benzodiazepine therapy.…”
Section: Discussionmentioning
confidence: 55%
“…1 Of the more than 22,000 unintentional pharmaceutical overdose deaths nationally in 2010, three-quarters involved opioid analgesics, while benzodiazepines were identified in one-quarter and antidepressants in nearly 20 %. 2 Concurrent use of these drugs appears to carry an even higher risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation